2010
DOI: 10.1177/0146167210383440
|View full text |Cite
|
Sign up to set email alerts
|

A Process Model of Affect Misattribution

Abstract: People often misattribute the causes of their thoughts and feelings. The authors propose a multinomial process model of affect misattributions, which separates three component processes. The first is an affective response to the true cause of affect. The second is an affective response to the apparent cause. The third process is when the apparent source is confused for the real source. The model is validated using the affect misattribution procedure (AMP), which uses misattributions as a means to implicitly me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(129 citation statements)
references
References 40 publications
2
126
1
Order By: Relevance
“…This, however, may not be sur-prising given individuals' inability to accurately detect the source of their affective states (e.g., Cantor, Zillmann, and Bryant 1975;Dutton and Aron 1974;Schwarz and Clore 1983). Individuals are especially likely to be unaware (and misattribute) the source of their affective arousal when the arousal source is not salient and when the arousal itself is relatively moderate (Gorn, Pham, and Sin 2001;Payne et al 2010;Vosgerau 2010). This seems especially likely in the present context.…”
Section: Discussionmentioning
confidence: 86%
“…This, however, may not be sur-prising given individuals' inability to accurately detect the source of their affective states (e.g., Cantor, Zillmann, and Bryant 1975;Dutton and Aron 1974;Schwarz and Clore 1983). Individuals are especially likely to be unaware (and misattribute) the source of their affective arousal when the arousal source is not salient and when the arousal itself is relatively moderate (Gorn, Pham, and Sin 2001;Payne et al 2010;Vosgerau 2010). This seems especially likely in the present context.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, they have the ability to tap into social cognitions that children might be unwilling to share, particularly at specific stages of development when their awareness of social expectations and norms begin to emerge (e.g., Rutland, Cameron, Milne, & McGeorge, 2005). The AMP, which was developed for use with adults (e.g., Gawronski, Cunningham, LeBel, & Deutsch, 2010;Inzlicht, Gutsell, & Legault, 2012;Payne, Burkley, & Stokes, 2008;Payne, Govorun, & Arbuckle, 2008;Payne, Hall, Cameron, & Bishara, 2010), has the potential to be a useful new implicit measure of children's attitudes.…”
Section: Assessing Children's Implicit Attitudes Using the Affect Mismentioning
confidence: 99%
“…The AMP builds on the classic principle that it is common for people to make misattributions about the origin of their thoughts, feelings, and behaviors (see Loersch & Payne, 2011;Payne et al, 2005;Payne et al, 2010, for reviews). Although people often believe that their judgments are under their conscious control, research has consistently demonstrated that subtle cues or primes in our environment can profoundly impact our cognitions, affect, and behavior (Hofmann & Wilson, 2010;Loersch & Payne, 2011).…”
Section: Assessing Children's Implicit Attitudes Using the Affect Mismentioning
confidence: 99%
See 1 more Smart Citation
“…Though such models were used originally in memory research, they have become popular in social psychology in the past decade (for reviews, see Payne & Bishara, 2009;Sherman et al, 2008). For instance, they have been used to disentangle the underlying processes of implicit measures of attitudes (Conrey et al ., 2005;Nadarevic & Erdfelder, 2011;Payne, 2001;Payne, Hall, Cameron, & Bishara, 2010;Stahl & Degner, 2007) as well as the processes contributing to person memory (Klauer & Wegener, 1998).…”
Section: A Multinomial Model Of the Smtmentioning
confidence: 99%